2003
DOI: 10.1088/0953-8984/15/33/304
|View full text |Cite
|
Sign up to set email alerts
|

The effects of anisotropy in Jahn–Teller systems: application to the icosahedralH  (h g) system

Abstract: Jahn–Teller (JT) coupling between electronic motion and lattice or molecular vibrations results in an adiabatic potential energy surface that contains either wells or troughs of minimum-energy points. When wells are lowest in energy, the system will vibrate about the minimum-energy points. This vibration must be taken into account when describing the quantum mechanical states of the system. In general, the wells will be intrinsically anisotropic. This anisotropy alters the vibrational frequencies and hence the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In previous papers that included anisotropy via the scale transformation, it was found that the energy of the states with no vibrational excitations should be calculated using a wavefunction equivalent to equation ( 19) corrected to second order in perturbation theory via coupling to phonon excited states on the upper APES sheets [42]. Second-order corrections to the states are necessary because the anisotropic corrections to the energy are second order.…”
Section: Results Including Anisotropymentioning
confidence: 99%
See 3 more Smart Citations
“…In previous papers that included anisotropy via the scale transformation, it was found that the energy of the states with no vibrational excitations should be calculated using a wavefunction equivalent to equation ( 19) corrected to second order in perturbation theory via coupling to phonon excited states on the upper APES sheets [42]. Second-order corrections to the states are necessary because the anisotropic corrections to the energy are second order.…”
Section: Results Including Anisotropymentioning
confidence: 99%
“…The sum is over µ and ν = θ and with b † and b defined in a similar manner b † θ and b θ . The µν are parameters which form a matrix whose values can be fixed by minimizing the energy of the ground state at a minimum-energy point calculated to second order in perturbation theory [39][40][41][42]. The effect of U s is to scale the Q ν according to the relation…”
Section: Anisotropic Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Corrections due to the anisotropy of the wells were introduced in Ref. 21. In the Appendix, Table II reports a few of the vibronic eigenenergies used to draw Fig.…”
Section: B the H ⊗ H Jtmentioning
confidence: 99%